CONCEPT ANALYSIS OF ADHERENCE TO ANTIRETROVIRAL THERAPY IN PEOPLE LIVING WITH HIV/AIDS - Zahra, Anggri Noorana; Waluyo, Agung; Yona, Sri (Universitas Aisyah Pringsewu, 2024)
HIV/AIDS remains a global health challenge, with adherence to antiretroviral therapy (ART) being crucial for its management. This comprehensive concept analysis explores adherence to ART in people living with HIV/AIDS, considering its multifaceted nature and the diverse factors influencing it. The purpose of this study was to explore the concept of adherence and define the operational definition of adherence to antiretroviral therapy in PLWH. Walker and Avant’s eight-step concept analysis was used in this study. The terms